PERENCANAAN STRUKTUR ATAS GEDUNG HOTEL FORT DE KOCK BUKITTINGGI - Yuli Nadia; Surya Eka Priana; Febrimen Herista (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The faster the population growth in a city, the greater the need for housing. Both permanent and temporary residence, where the need for housing will affect human activities / activities in a city. For that we need a temporary residence such as a hotel. Therefore, the hotel will be built vertically with a number of floors consisting of five floors. Planning of reinforced concrete buildings in this modern era is based on the application of engineering computer programs, one of which is the SAP2000 program. From the results of the structural analysis, structural reinforcement is obtained, based on the author's analysis the results obtained are, the material used is steel quality fy = 420 Mpa with concrete quality fc' = 24.9 Mpa.Keywords: Reinforced Concrete, SAP2000, Columns, Beams, Floor Plates